Trends, Growth, Production Instability and Export Dynamics Analysis of Basmati Rice in India - Dalal, Khushboo; Suman Ghalawat,; Girdhar, Amita; Goyal, Megha; Malik, Joginder Singh; Kaushal, Neelam; Sushma, (Indian Journal of Extension Education, 2024)
The research examined the trends, growth rates, and instability in Basmati rice production and export in India from 2001 to 2021. Secondary time series data on these parameters were collected from diverse sources including the official websites of the Department of Agriculture and Farmer’s Welfare, Directorate General of Commercial Intelligence, the Agricultural and Processed Food Product Export Development Authority (APEDA) and Statistics (DGCI&S) and Ministry of Commerce and Industry. Various analytical tools such as Compound Annual Growth Rate (CAGR) for growth rate analysis, Coefficient of Variation (CV), Coppock Instability Index, Cuddy Della Valle Index, and Index Number for instability analysis, and R-square for linear, second-degree, and polynomial regression for trend analysis were employed which served as a metric for goodness of fit. The analysis revealed significant insights into the dynamics of Basmati rice production and export over the study period. Notable findings include fluctuations in growth rates, trends indicating periods of acceleration or deceleration, and instability factors impacting production and export. These findings contribute to a deeper understanding of the Basmati rice industry in India, informing policymakers, stakeholders, and researchers for effective decision-making and strategic planning.